2018
DOI: 10.1108/ccij-05-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

It’s about how employees feel! examining the impact of emotional culture on employee–organization relationships

Abstract: Purpose The purpose of this paper is to examine the impact of emotional culture on the quality of employee–organization relationships (EORs). To understand the nuances of the influence of positive and negative emotional cultures on employee relational outcomes, this study specifically examined four fundamental emotional cultures, namely, joy, love, fear and sadness, in the cultivation of EORs. Further, as more recent emotional connotations of culture delve into the connections between employees’ fundamental ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 80 publications
1
14
0
1
Order By: Relevance
“…Finally, under the influence of Chinese culture, parents do not want their children to travel far. Moreover, the understanding of the nature of the project is different [18,19], which is an obstacle to the psychological inculcation of entrepreneurs. The essence of decision tree induction is to use a set of rules to classify the analyzed data.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Finally, under the influence of Chinese culture, parents do not want their children to travel far. Moreover, the understanding of the nature of the project is different [18,19], which is an obstacle to the psychological inculcation of entrepreneurs. The essence of decision tree induction is to use a set of rules to classify the analyzed data.…”
Section: Sample Collectionmentioning
confidence: 99%
“…It means that heart-based content optimization is an appropriate choice to impress and reach more users. Relatedness involves the feeling of being connected and cared for (Men and Robinson, 2018 ). A variety of positive emotions can spur the satisfaction of relatedness, such as joy (Baumeister and Leary, 1995 ), love, and enjoyment (Sternberg, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous strategic communication literature has suggested a variety of factors that can contribute to quality employee-organization relationships. These include, but are not limited to, leadership (e.g., Kelleher et al, 2019), communication strategies and climate (e.g., Jo & Shim, 2005), use of communication channels (e.g., Erjavec et al, 2018), organizational culture (e.g., Men & Robinson, 2018), structure (e.g., Grunig et al, 2002), and CSR activities (e.g., Chen et al, 2018). qualitative interviews with 27 Chinese startup leaders showed that startup CEOs' leadership communication plays a key role in building and cultivating relationships between startups and their employees.…”
Section: Employee-organization Relationships In the Startup Contextmentioning
confidence: 99%
“…In recent years, acknowledging the importance of cultivating positive relationships with employees, employee communication has earned growing scholarly attention in strategic communication research. Various studies have examined factors that influence relationships between an organization and its employees, with leadership and leadership communication playing a crucial role (e.g., Chen et al, 2018;Kelleher et al, 2019;Men & Robinson, 2018). Leadership communication can be particularly important in building relationships with employees at startups, because startup leaders are deeply involved in the implementation process as they lead through "direct involvement and by example" (Darling & Beebe, 2007, p. 76).…”
Section: Introductionmentioning
confidence: 99%